Reconstructing Greenland's climate.
Using ice-cores and a new isotopic method that can provide more precise temperature information, Marie Curie Fellow, Takuro Kobashi, has gained an insight into Greenland's climate history. His data, suggests Greenland's temperatures and global-sea-levels may increase faster than current climate projections.